Abaddons Gate (New York : Orbit, 2013)
An alien artifact working through its program under the clouds of Venus has emerged to build a massive structure outside the orbit of Uranus: a gate that leads into a starless dark. Jim Holden and the crew of the Rocinante are part of a vast flotilla of scientific and military ships going out to examine the artefact. But behind the scenes, a complex plot is unfolding, with the destruction of Holden at its core.
Keywords: Life on other planets -- Fiction; Space warfare -- Fiction; Conspiracies -- Fiction; Science fiction